Monday

June 27, 2016
Posted by **Brieson** on Friday, March 22, 2013 at 3:16pm.

- Algebra -
**Anonymous**, Friday, March 22, 2013 at 3:38pm3x^2 + 7x-6

(X+3)(3x-2) - Algebra -
**Reiny**, Friday, March 22, 2013 at 5:31pm3x^2 + 7x - 6

multiply the first and last coefficients

3(-6) = -18

factors of -18 that add up to 7

+9 and -2

(9)(-2) = -18 and 9 - 2 = 7

so replace the middle term of 7x with -2x + 9x

3x^2 - 2x + 9x -6

group as

(3x^2 - 2x) + (9x-6)

now factor each group

x(3x-2) + 3(3x-2)

= (3x-2)(x+3) - Algebra -
**silindokuhle**, Saturday, March 23, 2013 at 5:33amx=2/3 and x=-3